Refinement Of Apatite Ceramic Produced From Waste Dental Mould - William, Ng Kar Hong (Universiti Sains Malaysia, 2017)
According to Advanced Medical And Dental Institute USM (AMDI), the institute disposed 50 kg of dental mould waste per month. Dental mould waste was just thrown as medical waste. However, Dental mould waste has possibility of calcium source which can form apatite bioceramics materials when react with phosphoric acid. Bioceramics that can be synthesis from dental mould waste mainly Tricalcium Phosphate (TCP) or Hydroxyapatite (HA). In this study, it has two projects; synthesis apatite bioceramics from dental mould waste and heat treatment to dental mould waste to recycle it as raw material for making dental mould. The project of synthesis apatite bioceramics material, it adopts Chromite Ore Processing Residue (COPR), following by caustic leaching with 3M, 5M and 7M of Sodium Hydroxide (NaOH) solution. The result using 7M NaOH in caustic leaching was able to fully removed chromium content of leached residue and forming white color of apatite bioceramic material when react with Phosphoric acid. The main the phase of apatite material was Tricalcium Phosphate (TCP) after sintered in 1100 °C. For 2nd project, dental mould waste undergone heat treatment at 125 °C and 160 °C for 2 hour or 4 hour. Heat treatment product form main phase, which was Bassanite, one of the plaster of paris. Thus, preliminary result show it can be recycled to use as raw material for dental mould again.